Implementasi Metode Eksperimen Sederhana dalam Pengenalan Sains Kimia untuk Menstimulasi Kognisi Anak Usia Dini di Pelnap Pisga Abepura - Lusia Narsia Amsad; Rahmat Nurohman; Frans Deminggus; Arta Indah Pasaribu (Universitas Cenderawasih, 2025)
Early childhood science education plays a vital role in shaping children's cognitive structures, literacy, and numeracy. However, the general perception of chemistry as a complex discipline often acts as a barrier to its introduction at the elementary level. This community service activity aims to destigmatize this perception by introducing chemical science using simple, joyful learning experiment methods. The program was conducted at the Pentecostal Children's Service (PELNAP) of GPdI PISGA, Abepura, targeting the 5-12 age group. The intervention was carried out through two main experimental modules: volcanic eruption simulation and balloon inflation via chemical gas reaction. The implementation methods included demonstration stages, guided independent experiments, and participatory observation. The results showed a significant increase in children's attention and intrinsic interest in scientific phenomena. Through an inquiry-based approach, children were able to understand the basic concepts of acid-base reactions producing carbon dioxide (CO2) gas in a concrete manner. It is concluded that the integration of experiment methods based on natural materials is effective in stimulating scientific curiosity and children's cognitive development, while offering an interactive science learning alternative outside the formal school environment.